2002
DOI: 10.1046/j.1365-2133.2002.04834.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of niacinamide on reducing cutaneous pigmentation and suppression of melanosome transfer

Abstract: The data suggest niacinamide is an effective skin lightening compound that works by inhibiting melanosome transfer from melanocytes to keratinocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
286
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(301 citation statements)
references
References 18 publications
(25 reference statements)
10
286
0
5
Order By: Relevance
“…In vitro, centaureidin [99], a flavone from Achillea millefolium (common yarrow), and methylophiopogonanone B [100] (MOPB), a homoisoflavonoid from Ophiopogon japonicus (mondo grass), block melanosome transfer by inducing the retraction of melanocyte dendrites through activation of GTPase Rho (the master regulator of dendrite formation in melanocytes) [101]). Niacinamide (the amide form of vitamin B3), inhibits melanosome transfer in vitro and has a significant effect in reducing hyperpigmentation in vivo, although its mode of action is not known [102]. Another in vitro study showed that plasma membrane lectins and their glycoconjugates interfere with melanocyte-keratinocyte interactions by binding to their specific plasma membrane receptors and inhibiting melanosome transfer [103].…”
Section: Biological Effectorsmentioning
confidence: 99%
“…In vitro, centaureidin [99], a flavone from Achillea millefolium (common yarrow), and methylophiopogonanone B [100] (MOPB), a homoisoflavonoid from Ophiopogon japonicus (mondo grass), block melanosome transfer by inducing the retraction of melanocyte dendrites through activation of GTPase Rho (the master regulator of dendrite formation in melanocytes) [101]). Niacinamide (the amide form of vitamin B3), inhibits melanosome transfer in vitro and has a significant effect in reducing hyperpigmentation in vivo, although its mode of action is not known [102]. Another in vitro study showed that plasma membrane lectins and their glycoconjugates interfere with melanocyte-keratinocyte interactions by binding to their specific plasma membrane receptors and inhibiting melanosome transfer [103].…”
Section: Biological Effectorsmentioning
confidence: 99%
“…Niacinamide was found to decrease hyperpigmentation compared with placebo alone after 4 weeks of use in a study to assess the melanogenesis in vitro and facial hyperpigmentation and skin colour in vivo in Japanese women. 18 Considering the beneficial effects of these botanicals, the objective of the study was to assess the effectiveness of the study medication containing a combination of niacinamide 4.0%, glycolic acid 2.0%, vitamin E acetate 0.1%, kojic acid dipalmitate 2.0%, soy isoflavones 0.5%, arbutin 2.0%, pterowhite 0.12%, licorice 40% CA 0.12% and ascorbyl glucoside 0.1% in the treatment of epidermal pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…One can assume that antioxidants, particularly ascorbic acid [18] [20], niacinamide [21] and GSH [22] have skin whitening properties. Niacinamide is a well-known vitamin that decreases melanosome transfer [23] with a very interesting light effect [24]. As for ascorbic acid, it interacts with copper ion at the tyrosinase activity site with strong antioxidant properties [25] and anti-inflammatory effects [20] (Figure 6 and Figure 7).…”
Section: Discussionmentioning
confidence: 99%